Pengaruh Pendekatan Bridging Analogy Terhadap Kemampuan Pemahaman Konsep Matematis Siswa SMP - Rachmatya, Nalurita Wening; Firdausi, Firdausi; Dwirahayu, Gelar (Media Pendidikan Matematika, 2025)
Conceptual understanding in mathematics is an essential competency that students must master to achieve learning objectives. This study aims to determine the effect of the Bridging Analogy approach on students’ conceptual understanding of mathematics in Grade VIII at a junior high school in South Jakarta during the 2025/2026 academic year. The research employed a quasi-experimental method with a randomized two group post-test only design, involving two sample groups: class VIII C ar the experimental group and class VIII B as the control group, each consisting of 33 students. The research instrument consisted of a multiple-choice test with 30 items on the topic of relations and functions. Data were analyzed using the t-test with the aid of SPSS software. The results showed that the experimental group obtained an average score of 64.34 with a variance of 201.03, while the control group achieved an average score of 52.73 with a variance of 201.01. The hypothesis testing yielded at t-value 0f 3.328, which was greater than the t-table value of 1.998 at a 5% significance level, thus the alternative hypothesis was accepted. Therefore, it can be concluded that the implementation of the Bridging Analogy approach significantly improves students’ mathematical conceptual understanding. However, despite the statistical significance, the average score has not yet reached the minimum mastery criterion, suggesting the need for further practical improvements.